2000
DOI: 10.1021/bi000788y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architecture of the Mutagenic Active Site of Human Immunodeficiency Virus Type 1 Reverse Transcriptase:  Roles of the β8-αE Loop in Fidelity, Processivity, and Substrate Interactions

Abstract: Human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) is a putative source of the genomic hypermutation that promotes rapid evolution of HIV-1. To understand the molecular strategies that create a highly mutagenic DNA polymerase active site in HIV-1 RT, we investigated the roles of four residues in the beta 8-alpha E loop. Gln151, which interacts with the sugar of the incoming dNTP, and Lys154, which interacts with the template, yielded site-directed mutants with increased fidelity, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
58
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 33 publications
(76 reference statements)
9
58
1
Order By: Relevance
“…Data from single nucleotide steady state kinetic assays using the Q151N mutant also substantiated our findings (22). Structural examination showed that the wild type Gln 151 residue interacts with the 3Ј-OH on the sugar moiety of the incoming dNTP (21). It has been suggested that this interaction between the Gln 151 residue and the 3Ј-OH of the incorrect dNTP stabilizes RT binding to the incorrect dNTP.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Data from single nucleotide steady state kinetic assays using the Q151N mutant also substantiated our findings (22). Structural examination showed that the wild type Gln 151 residue interacts with the 3Ј-OH on the sugar moiety of the incoming dNTP (21). It has been suggested that this interaction between the Gln 151 residue and the 3Ј-OH of the incorrect dNTP stabilizes RT binding to the incorrect dNTP.…”
supporting
confidence: 83%
“…Recently, we reported that the Q151N mutant has 12.5 times higher fidelity than wild type HIV-1 RT based on the M13 lacZ␣ forward mutation assay (21). Data from single nucleotide steady state kinetic assays using the Q151N mutant also substantiated our findings (22).…”
supporting
confidence: 80%
“…Hexahistidine-tagged HXB2 HIV-1 RT gene (23) was introduced into pET28a (Novagen) and overexpressed in BL21 Escherichia coli (Novagen). The RT protein was purified using Ni 2ϩ chelating chromatography as described previously (24,25). The concentration and purity of the protein was analyzed by 10% SDSpolyacrylamide gel using 1.5 g of bovine serum albumin (Sigma) as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Our observation that Gln 151 mutations result in AZT hypersensitivity was unexpected, since a methionine substitution at this site confers weak AZT resistance in clinical isolates, and the combination of four additional mutations with Q151M results in high level resistance to AZT and several other nucleoside analogs (46,47) (Table I). Analyses of purified RTs show that the Q151M and Q151N mutations confer resistance to nucleoside analogs as well as mild to moderate increases in the fidelity of nucleotide incorporation in cell-free assays (11,55,56). Substitutions of alanine or asparagine at the equivalent position of murine leukemia virus RT (Gln 190 ) also confer increased fidelity but render the enzyme hypersensitive to dideoxynucleoside triphosphates (57).…”
Section: Discussionmentioning
confidence: 99%
“…Two lines of evidence support this suggestion. First, biochemical analyses of mutant RTs and RDRPs have identified a number of amino acid replacements in motif B that severely compromise polymerase activity (7)(8)(9)(10)(11)(12)(13)(14)(15). Second, the primary sequence of motif B is strictly conserved in independent virus isolates; in human immunodeficiency virus type-1 (HIV-1), this region is nearly invariant (16).…”
mentioning
confidence: 99%